2020
DOI: 10.3390/biom10091240
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Functions of Connexin 43 during the Development of Primary or Secondary Bone Tumors

Abstract: Despite research and clinical advances during recent decades, bone cancers remain a leading cause of death worldwide. There is a low survival rate for patients with primary bone tumors such as osteosarcoma and Ewing’s sarcoma or secondary bone tumors such as bone metastases from prostate carcinoma. Gap junctions are specialized plasma membrane structures consisting of transmembrane channels that directly link the cytoplasm of adjacent cells, thereby enabling the direct exchange of small signaling molecules bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 199 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…The permeability of Cx43 channels to small molecules and macromolecules makes them very attractive targets for delivering drugs directly to the cytoplasm. Cancer cells that overexpress Cx43 may be more permeable and sensitive to chemotherapeutics ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The permeability of Cx43 channels to small molecules and macromolecules makes them very attractive targets for delivering drugs directly to the cytoplasm. Cancer cells that overexpress Cx43 may be more permeable and sensitive to chemotherapeutics ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transcript levels of these candidates were elevated at least two times in OS tissues. We previously showed that extracellular histone H4 and PPIB acted as tumor-suppressing proteins in breast cancer ( Liu et al, 2021a , Sun et al, 2021 ), while the five others were reported to stimulate the progression of OS when present in the intracellular domain ( Chen et al, 2021 ; Wang et al, 2019 ; Zhang et al, 2021 ; Talbot et al, 2020 ; Zhou et al, 2018 ). To examine anti-tumor capabilities, we employed the recombinant proteins (MBS553651, MBS2097677, MBS2009092, MBS2029317, MBS146520, MBS2557159, MBS2031097; MyBioSource), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The transcript levels of these candidates were elevated at least 2 times in OS tissues. We previously showed that extracellular Histone H4 and PPIB acted as tumor-suppressing proteins in breast cancer (Sano et al, 2021, Sun et al, 2021), while the five others were reported to stimulate the progression of OS when present in the intracellular domain (Chen et al, 2021, Wang et al, 2019, Zhang et al, 2021, Talbot et al, 2020, Zhou et al, 2018). To examine anti-tumor capabilities, we employed the recombinant proteins (MBS553651, MBS2097677, MBS2009092, MBS2029317, MBS146520, MBS2557159, MBS2031097; MyBioSource), respectively.…”
Section: Methodsmentioning
confidence: 99%